Duration of resuscitation efforts for in-hospital cardiac arrest by predicted outcomes: Insights from Get With The Guidelines − Resuscitation. (April 2017) - Bradley, Steven M.; Liu, Wenhui; Chan, Paul S.; Girotra, Saket; Goldberger, Zachary D.; Valle, Javier A.; Perman, Sarah M.; Nallamothu, Brahmajee K.; ,
Abstract: Background: The duration of resuscitation efforts has implications for patient survival of in-hospital cardiac arrest (IHCA). It is unknown if patients with better predicted survival of IHCA receive longer attempts at resuscitation. Methods: In a multicenter observational cohort of 40, 563 adult non-survivors of resuscitation efforts for IHCA between 2000 and 2012, we determined the pre-arrest predicted probability of survival to discharge with good neurologic status, categorized into very low (<1%), low (1–3%), average (>3%–15%), and above average (>15%). We then determined the association between predicted arrest survival probability and the duration of resuscitation efforts. Results: The median duration of resuscitation efforts among all non-survivors was 19 min (interquartile range 13–28 min). Overall, the median duration of resuscitation efforts was longer in non-survivors with a higher predicted probability of survival with good neurologic status (median of 16, 17, 20, and 23 min among the groups predicted to have very low, low, average, and above probabilities, respectively; P < 0.001). However, the duration of resuscitation was often discordant with predicted survival, including longer than median duration of resuscitation efforts in 40.4% of patients with very low predicted survival and shorter than median duration of resuscitation efforts in 31.9% of patients with above average predicted survival. Conclusions: The duration of resuscitation efforts in patients with IHCA was generally consistent with their predicted survival. However, nearly a third of patients with above average predicted outcomes received shorter than average (less than 19 min) duration of resuscitation efforts.